The Validity of Learning Media Using Prezi Application Equipped with a Guidebook on Biodiversity Material for Students of Class X SMA - Relsas Yogica; Armen Armen; Sa'diatul Fuadiyah; Eka Rahma Juwita (ATRIUM PENDIDIKAN BIOLOGI, 2019)
The development of Science and Technology (IPTEK) is so rapidly affecting the use of electronic technology in learning. Teachers are expected to be able to use multimedia in learning. One example of multimedia utilization in learning is the application for learning media in addition to PowerPoint presentations, namely the Prezi application. Prezi is an application that is used to make presentations more interesting. Prezi can contain text, images, videos and other presentation media placed on the presentation canvas and can be grouped in frames that have been provided. Most of the teachers who are not able to apply multimedia especially the Prezi application, it is necessary to have a guidebook to use the Prezi application so that teachers and students are able to use the application as a medium for learning. Therefore, the purpose of this study is to produce learning media using the Prezi application equipped with a guidebook on biodiversity material for high school class X students who are valid and practical.This type of research is research and development development research using the Instructional Development (IDI) model. The object of this research is learning media using the Prezi application equipped with a guidebook on biodiversity material for class X students. The subjects of this study were 30 students of class X high school UNP Laboratory Development as the practicality of using the Prezi application and guidebook and validation by 2 people Biology Department lecturer FMIPA UNP and 1 Biology High School teacher Development UNP Laboratory.Based on the results of the study, it was found that the results of the validation showed an average value of 89.93 in the valid category. This shows that the learning media using the Prezi application equipped with a guidebook was developed valid both in terms of feasibility aspects of content, language, presentation and aspects of graphics.